2000
DOI: 10.4054/demres.2000.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of divorce in a traditional Muslim community in Bangladesh

Abstract: This study examines the effects of spouses' prior marital status and socio-demographic characteristics on the risk of divorce of 1762 Muslim marriages recorded in 1982-83 in Teknaf, Bangladesh. Grooms' prior marital status was categorized into never married, divorced, widowed or polygynous (already cohabiting with one or more wives) and brides' prior marital status was categorized into never married, divorced or widowed. Divorce was recorded by following the marriages prospectively for five years. Due to the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…Bhuiya et al (2005) using this data show that for Muslim marriages that occurred between 1980 and 1987, nearly 13 percent ended in divorce by the end of the ninth year. An earlier study by Alam et al (2000) for the same region tracked marriages that occurred between 1975 and 1979 for 13-17 years and found that nearly one-third of them ended in divorce. While the two studies are not directly comparable because the duration of marriage is different, the magnitude of the difference is so large that it cannot be merely attributed to duration of marriage, suggesting a real decline in divorce rates.…”
Section: South Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…Bhuiya et al (2005) using this data show that for Muslim marriages that occurred between 1980 and 1987, nearly 13 percent ended in divorce by the end of the ninth year. An earlier study by Alam et al (2000) for the same region tracked marriages that occurred between 1975 and 1979 for 13-17 years and found that nearly one-third of them ended in divorce. While the two studies are not directly comparable because the duration of marriage is different, the magnitude of the difference is so large that it cannot be merely attributed to duration of marriage, suggesting a real decline in divorce rates.…”
Section: South Asiamentioning
confidence: 99%
“…While the two studies are not directly comparable because the duration of marriage is different, the magnitude of the difference is so large that it cannot be merely attributed to duration of marriage, suggesting a real decline in divorce rates. In fact, analysis by Alam et al (2000) for earlier periods shows that divorces per thousand married males declined between 1975-1979 and 1989-1992. In conservative parts of Bangladesh, divorce was high. In Teknaf, a conservative Muslim region bordering Myanmar, there were nearly 30 divorces for 100 marriages in the early 1980s (ibid.).…”
Section: South Asiamentioning
confidence: 99%
“…Other determinants of marital dissolution that have been examined in previous studies (but will not be investigated here due to data limitations) include female employment, age differences between spouses, presence of children, marital duration, and previous history of marital breakdown (Alam, Saha, and van Ginneken 2000;Bhuiya et al 2005;Dommaraju 2016;Jennings 2016).…”
Section: Other Factorsmentioning
confidence: 99%
“…One of the enduring findings in studies of the determinants of divorce is the significant role of age at marriage (Carmichael 1988;Alam, Saha, and van Ginneken 2000;Heaton, Cammack, and Young 2001;Hirschman and Teerawichitchainan 2003;Teerawichitchainan 2004;Jennings 2016). Individuals who marry at a young age are more likely to divorce because they are less mature and less knowledgeable, are still caught up in the rapid changes that they go through in their adolescent years, and spend less time searching for compatible partners (Booth and Edwards 1985;South and Spitze 1986;Thornton and Rogers 1987).…”
Section: Age At Marriagementioning
confidence: 99%
“…The rate of divorce is also found higher in first three years of marriage than longer duration. The low socio-economic status of spouse, illiteracy and early marriage increase the odds of divorce (Alam et al 2000). It's a social phenomenon like marriage and sanctioned arrangement to terminate the marriage formally and dissolve the family group (Bertrand 1967).…”
Section: Literature Reviewmentioning
confidence: 99%